Preparation of corrosion-resistant surface of magnesium alloy and its performance study - Shimeng Li; Baofu Sun (Materials Research Express, 2023)
The susceptibility of magnesium alloys to corrosion has hindered the wide application of magnesium alloys. A natural green method was proposed in this study to prepare a corrosion-resistant film layer whose main substance is MgO on the magnesium alloy substrate by a two-step hydrothermal method combining water steaming and annealing treatment. The morphology, composition, structure and corrosion resistance of the coating were investigated by SEM, FTIR, XRD and electrochemical methods. The results showed that the prepared coating has excellent corrosion resistance, reducing corrosion current by about four orders of magnitude compared with the bare Mg alloy substrate, and the corrosion potential and corrosion rate are also increased in different degree.